Development of an Android-Based Educational Game Application on the Human Respiratory System Material for Fifth Grade Elementary School Students - Jodhi Muhamad Zuhair; Tedi Budiman (RISTEC : Research in Information Systems and Technology, 2025)
Natural Science (IPA) is one of the compulsory subjects taught at the elementary school level. The content of this subject is quite broad and complex, making it often difficult for students to understand and requiring appropriate learning media to support concept comprehension. One of the topics considered complex is the human respiratory system. To help students understand the material more effectively, engaging learning media that suit their characteristics are needed. Elementary school students generally have a strong interest in playing games; therefore, developing game-based learning media is a relevant solution.This study aims to design and develop a learning media in the form of an Android-based educational game application named game edukasi for the Natural Science subject, focusing on the human respiratory system topic. The research employs the Design and Development (DnD) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation.The research results show that: (1) the game edukasi educational game application was successfully developed and can be used by both teachers and students in the learning process; (2) the feasibility assessment by media and material experts resulted in a “very feasible” category; and (3) user responses toward the application were in the “very good” category. Therefore, the game edukasi educational game application is considered feasible to be used as a learning medium for the human respiratory system topic in Natural Science learning.